2019
DOI: 10.7150/jca.28111
|View full text |Cite
|
Sign up to set email alerts
|

Genistein inhibits human papillary thyroid cancer cell detachment, invasion and metastasis

Abstract: Papillary thyroid carcinoma (PTC) is the most commonly diagnosed endocrine cancer, and those with BRAFV600E mutation have high recurrence rate and less favorable clinical behavior. Genistein having anti-carcinoma effects in various types of carcinomas as an estrogen analog, but the mechanism of Genistein in the progression of PTC remains unknown. Genistein significantly inhibits the proliferation and the invasion (P < 0.01), and the apoptosis (P < 0.001) of all tumor cell lines, which was probably due to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…Deregulated activation of the BRAF V600E-dependent MAPK/ERK effectors is best recognized in the mechanisms underlying melanoma genesis and the growth of papillary thyroid cancer [32,55,56]. A predominantly similar phenotype is caused by the V600E mutation, including enhanced invasion, proliferation, and metastasis [32,55,56]. Our studies showed a significant similarity of the influence of BRAF V600E on the characteristics of THLE-2 cells, which may indicate a strong invasive and migration effect of this mutation in the liver tissue.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Deregulated activation of the BRAF V600E-dependent MAPK/ERK effectors is best recognized in the mechanisms underlying melanoma genesis and the growth of papillary thyroid cancer [32,55,56]. A predominantly similar phenotype is caused by the V600E mutation, including enhanced invasion, proliferation, and metastasis [32,55,56]. Our studies showed a significant similarity of the influence of BRAF V600E on the characteristics of THLE-2 cells, which may indicate a strong invasive and migration effect of this mutation in the liver tissue.…”
Section: Discussionsupporting
confidence: 59%
“…Constant activation of the MAPK/ERK pathway promotes cell migration, proliferation, and the tumor microenvironment [54]. Deregulated activation of the BRAF V600E-dependent MAPK/ERK effectors is best recognized in the mechanisms underlying melanoma genesis and the growth of papillary thyroid cancer [32,55,56]. A predominantly similar phenotype is caused by the V600E mutation, including enhanced invasion, proliferation, and metastasis [32,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…The human ATC cell lines 8305C (RRID: CVCL_1053), BHT101 (RRID: CVCL_1085) and KMH-2 (RRID: CVCL_S641) were kindly provided by the Stem Cell Bank, Chinese Academy of Sciences (Shanghai, China). The PTC cell line BHP10-3 (RRID: CVCL_6278) was obtained from Qilu Hospital of Shandong University [ 23 ]. All cell lines that were authenticated using STR profiling within the last 3 years were included.…”
Section: Methodsmentioning
confidence: 99%
“…Genistein is the main active ingredient of Leguminosae. is isoflavone inhibits the invasion and metastasis of the PTC-derived BHP10-3 cell (with RET/PTC 1 rearrangement), BCPAP, and IHH4 (with BRAF V600E mutation) by inhibiting β-catenin and EMT [46]. However, genistein upregulates most thyroid transcript signals, except for thyroid peroxidase, in zebrafish embryos, thereby indicating potential disruptions [105].…”
Section: Flavonoidsmentioning
confidence: 99%